THE ROLE OF BRAND AWARENESS IN MEDIATING THE EFFECT OF SOCIAL MEDIA AND ELECTRONIC WORD OF MOUTH ON PURCHASE INTENTION FOR EMINA SKINCARE IN TIKTOK SHOP - Nawari; Shoimah, Siti; Qomariyah, Nur (International Journal of Multidisciplinary Reseach, 2025)
The rapid development of digital technology has significantly influenced marketing strategies, particularly through the utilization of Social Media and Electronic Word of Mouth (e-WOM) as effective promotional tools. Emina, as one of the skincare brands, leverages TikTok Shop to enhance its product sales. This study aims to analyze the influence of Social Media and e-WOM on Purchase Intention, with Brand Awareness serving as a mediating variable. This research employed a quantitative approach using a purposive sampling technique. Data were collected through questionnaires distributed to TikTok Shop users who had seen or purchased Emina skincare products, involving a total of 128 respondents. The findings indicate that Social Media and e-WOM have a positive and significant effect on Purchase Intention. Furthermore, Brand Awareness was found to significantly mediate the relationship between Social Media, e-WOM, and Purchase Intention. These results suggest that increasing promotional interactions through Social Media and positive consumer reviews can strengthen brand awareness, ultimately enhancing consumers’ purchase intention of Emina skincare products on TikTok Shop.